The “Kabedon” technique for treatment of abdominal aortic aneurysm with severe angulation of infrarenal aortic neck - Sun, Xiaozhi; Huang, Wenjing; Ma, Huibo; Qu, Hongyu; Zhang, Heng; Yan, Junwei; Jiao, XueFei; Liu, Junjun; Guo, Mingjin (Frontiers in Surgery, 2025)
ObjectiveTo evaluate the feasibility and short-term clinical outcomes of the Kabedon technique-based endovascular aneurysm repair (EVAR) for abdominal aortic aneurysms (AAA) with severe infrarenal neck angulation (angle >60°).MethodsThis retrospective cohort study was based on a single-center database. Between January 2019 and May 2023, 120 patients with AAA of hostile neck angulation underwent endovascular procedures using the Kabedon technique for abdominal aortic remodeling. A standardized protocol was followed to calculate the serial changes in the aneurysmal neck angle. The primary endpoints were proximal type Ia endoleak and stent-graft migration. The secondary endpoints were all-cause and aneurysm-related mortality, proximal neck dilatation, and re-intervention.ResultsThe mean age was 71.40 ± 10.69 years, and 95 (79.17%) were male. The mean AAA sac diameter and proximal neck angle were 63.71 ± 17.32 mm and 83.67 ± 18.45°, respectively. All patients underwent the Kabedon-based EVAR, with a technical success rate of 94.17% (113/120). During the operation, 7 cases of endoleak and 2 cases of endograft migration were observed, which were resolved by corresponding measures such as coil embolization and proximal cuff stent salvage. No complications were observed within 30 days. In addition, neck calcification, funnel-shaped aneurysm, intraoperative complications and corresponding treatments may be potential negative factors for technical success, but there was no statistical difference.ConclusionsKabedon-based EVAR for AAA with a severely angulated neck provided high technical success, low mortality and complication rates during short-term follow-up. Further studies with larger sample sizes and longer follow-up periods are warranted.